Controlling of the photosensing properties of Al/DMY/p-Si heterojunctions by the interface layer thickness - Imer, A. Gencer; Karaduman, O.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2016)
Organic-inorganic heterojunction was fabricated by inserting an interlayer having with three different thicknesses on the p-Si substrate. The current voltage (I-V) data of different samples were measured both under the dark and solar simulator at 300 K. The photosensing properties of devices were analyzed as a function of incident light intensity via I-V data by considering the influence of different light intensity on the generated electron-hole pairs. The transient photocurrent measurement confirmed that the photocurrent is sensitive to the illumination intensities. The obtained results confirmed that photo sensing nature and responsivity of heterojunctions enhance with the illuminations. The electrical characteristic of different heterojunctions was also obtained from voltage dependent capacitance (C-V), conductance (G-V) data as a function of frequencies. The excess capacitance could not be observed at highly enough frequencies because of that interface states charge cannot follow ac signal. The density of interface states (D-it) was evaluated by Hill-Coleman method and changes in the range from similar to 1.05 x 10(12) to 9.69 x 10(10) eV(-1) cm(-2) with the increasing frequency. It is declared that, photosensing property of diode can be controlled by various thickness of the interface layer. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dimethyl yellow; Organic material; Heterojunction; Photosensing; Barrier height; Ideality factor